Humidity and temperature sensing properties of 2-(Z)-[1-(ethoxycarbonyl)-2-oxopropyl]diazenylbenzoic acid. (10th January 2020) - Shah, Mutabar; Anwar, Kashif; Khan, Rasool
Abstract: In this paper, surface type 2-( Z )-[1-(ethoxycarbonyl)-2-oxopropyl]diazenylbenzoic acid ( Z -ECODBA) based humidity and temperature sensors have been fabricated and investigated. Thin films of aluminum electrodes and organic semiconductor ( Z -ECODBA) were thermally deposited onto the surface of a cleaned glass substrate using Edward Auto 306 thermal evaporator. The surface morphology of the active thin film of Z -ECODBA was studied using Scanning Electron Microscopy (SEM). The humidity dependent capacitive and resistive responses of Z -ECODBA based sensors were studied in the relative humidity range of 40% RH to 90% RH at different applied frequencies. The results showed that the capacitance increased nonlinearly with the increasing relative humidity level, while the resistance decreased and vice versa. The value of capacitance increased 1551.43, 628.18, 376.96, 119 and 71 times for sample (A), 848.75, 350, 175, 112.5 and 50 times for sample (B), 691.45, 275, 177.34, 69.87 and 48.6 times the sample (C) at 0.1, 0.5, 1, 5 and 10 kHz, respectively. The decrease in resistance was observed 26712.09, 1281.11, 1130, 578.60 and 173.41 times for sample (A), 23327.29, 1992.307, 7047.36, 22455.55 and 12400 times for the sample (B) and 29435.72, 5341.86, 3732.25, 2642.10 and 1495 times for sample (C) at a frequency of 0.1, 0.5, 1, 5 and 10 kHz, respectively. The effect of temperature on the capacitance of the fabricated samples was investigated at three different applied frequencies of 0.1 kHz, 0.5 kHz and 1 kHz, respectively. The capacitance has also been observed to increase with the rise in temperature. Moreover, the capacitance was found to decrease while resistance was observed to increase with the increasing inter electrodes gap. The response and recovery times were recorded 30 s and 21 s for sample of 25 μ m, 27 s and 21 s for sample of 40 μ m and 27 s and 27 s for sample of 50 μ m inter electrodes gape, respectively.